A critical review of stock market development in India. Issue 1 (21st August 2020) - Salameh, Samer; Ahmad, Asad
Abstract : The development of stock markets in the financial sector has been important. The expansion of stock markets has compelled various researchers to analyze its relationship with the economic process and development of countries. The studies have revealed that the performance of stock markets in a nation has a positive correlation to its economic growth. Bearing this relationship in mind, studies are being undertaken to recognize the elements responsible for stock market development in several nations. The researchers all around the world are trying to better understand determinants so that government establishments can create and target policies that may help the development of stock markets which further helps in economic development of the state. Throughout the past three decades, the global stock markets surged, and emerging markets played a vital role in this boom. Recent researches have begun to concentrate on the linkages between the stock markets and economic development. There has been an extensive analysis of the connection between the stock market and economic growth, but there is a dearth of theoretical empirical proof on what determines stock exchange development. Keeping in view the importance of stock markets in the development of economic development, the researchers in the present study have tried to bring out the factors that play a positive role in the development of stock market.